Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
ĐKXĐ : \(x+2\ge0\Rightarrow x\ge-2\)
=> |x| = x + 2
<=> \(\orbr{\begin{cases}x=x+2\\x=-x-2\end{cases}}\Rightarrow\orbr{\begin{cases}0x=2\left(\text{loại}\right)\\2x=-2\end{cases}\Rightarrow x=-1\left(tm\right)}\)
b) ĐKXĐ \(x\ge0\)
=> |x - 1| = x
<=> \(\orbr{\begin{cases}x-1=x\\-x+1=x\end{cases}}\Rightarrow\orbr{\begin{cases}0x=1\left(\text{loại}\right)\\2x=1\end{cases}\Rightarrow x=0,5\left(tm\right)}\)
c) ĐKXĐ \(2x-3\ge0\Rightarrow x\ge1,5\)
Khi đó : \(x-1\ge0;x+1\ge0\)
Ta có |x - 1| + |x + 1| = 2x - 3
<=> x - 1 + x + 1 = 2x - 3
=> 2x = 2x - 3
=> 0x = -3 (loại)
Vậy \(x\in\varnothing\)
TH 1: \(x;y\le0\)
=> \(\left|x\right|+\left|y\right|=-x+\left(-y\right)\)và \(x+y\le0\)
=> \(\left|x+y\right|=-\left(x+y\right)=-x+\left(-y\right)\)
=> \(\left|x\right|+\left|y\right|=\left|x+y\right|\)\(\left(1\right)\)
TH 2: \(x\le0;y\ge0;x+y\le0\)
=> \(\left|x\right|+\left|y\right|=-x+y\)và \(\left|x+y\right|=-\left(x+y\right)=-x+\left(-y\right)\)
Mà \(y\ge0\)
=> \(y\ge-y\)
=> \(-x+y\ge-x+\left(-y\right)\)
=> \(\left|x\right|+\left|y\right|\ge\left|x+y\right|\)\(\left(2\right)\)
TH 3: \(x\le0;y\ge0;x+y\ge0\)
=> \(\left|x\right|+\left|y\right|=-x+y\)và \(\left|x+y\right|=x+y\)
Mà \(x\le0\)
=> \(-x\ge x\)
=> \(-x+y\ge x+y\)
=> \(\left|x\right|+\left|y\right|\ge\left|x+y\right|\)\(\left(3\right)\)
TH 4: \(x\ge0;y\le0;x+y\le0\)
=> \(\left|x\right|+\left|y\right|=x+\left(-y\right)\)và \(\left|x+y\right|=-\left(x+y\right)=-x+\left(-y\right)\)
Mà \(x\ge0\)
=> \(x\ge-x\)
=> \(x+\left(-y\right)\ge-x+\left(-y\right)\)
=> \(\left|x\right|+\left|y\right|\ge\left|x+y\right|\)\(\left(4\right)\)
TH 5: \(x;y\ge0\)
=> \(\left|x\right|+\left|y\right|=x+y\)và \(\left|x+y\right|=x+y\)
=> \(\left|x\right|+\left|y\right|=\left|x+y\right|\)\(\left(5\right)\)
Từ (1), (2), (3), (4), và (5) => \(\left|x\right|+\left|y\right|\ge\left|x+y\right|\)
Ta có: \(\frac{x+1}{2019}+\frac{x+1}{2020}=\frac{x+1}{2021}\)
\(\Leftrightarrow\frac{x+1}{2019}+\frac{x+1}{2020}-\frac{x+1}{2021}=0\)
\(\Leftrightarrow\left(x+1\right)\left(\frac{1}{2019}+\frac{1}{2020}-\frac{1}{2021}\right)=0\)
Mà \(\frac{1}{2019}+\frac{1}{2020}-\frac{1}{2021}>0\)
\(\Rightarrow x+1=0\Rightarrow x=-1\)
\(\frac{x+1}{2019}+\frac{x+1}{2020}=\frac{x+1}{2021}\)
\(\frac{x+1}{2019}+\frac{x+1}{2020}-\frac{x+1}{2021}=0\)
\(\left(x+1\right)\left(\frac{1}{2019}+\frac{1}{2020}-\frac{1}{2021}\right)=0\)
\(x+1=0\left(\frac{1}{2019}+\frac{1}{2020}-\frac{1}{2021}\ne0\right)\)
\(x=0-1=-1\)